Sustained Release of Captopril Tablet with Floating System Using a Cross-Linked Matrix of Alginate - Dhadhang Wahyu Kurniawan; Dike Agus Triyanto; Vitis Vini Fera Ratna Utami (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2018)
Captopril has a short biological half-life 2-3 hours and has been used for long-term treatment of hypertension. The properties of captopril such as absorbed well in the stomach, freely water-soluble, instability in intestinal environment, and bioavailability about 65%. This study aimed to determine the physical characteristics and drug release profile of captopril tablet sustained release with a floating system using a cross-linked matrix of alginate with calcium chloride as a crosslinker. Matrix system was obtained by forming alginate cross-linked with a calcium chloride. HPMC K4M was used to help cross-linking reaction. Tablet was prepared by wet granulation with varying levels of sodium alginate and calcium chloride. Dissolution test is carried out by paddle method in HCl pH 1,2; 100 rpm; and 37Â±0,5oC for 8 hours. Amount of captopril released determined by measuring the captopril dissolved using UV spectrophotometry at Î» 205 nm. The result showed that this tablet having physical characteristics suitable with the general requirements for tablets. Drug release profile of captopril tablet sustained release with a floating system using a cross-linked matrix of alginate with calcium chloride as a crosslinker capable keeping release of captopril up to 8 hours (third formula) about 51,226% (DE) and followed zero order kinetics.Â